Investigating the Impact of “other foods” on Aboriginal Children’s Dietary Intake Using the Healthy Eating Index – Canada (HEI-C) - Chard, Megan (University of Waterloo, 2010)
Introduction: The high prevalence of obesity in Aboriginal Canadian youth is a major public health concern. Although little is known about the diets of children on-reserve, it is hypothesized that high intake of low nutrient dense foods has a negative impact on overall diet quality. Objectives: To describe the dietary quality of First Nation students using a Canadian adaptation of the Healthy Eating Index (HEI-C) and determine the relationships between HEI-C and BMI, intake of non-food group (“other”) foods, game consumption, frequency of eating outside the home and remoteness (latitude, °N). Methods: Between 2004-2009, from a 24 h dietary recall data were obtained using a validated web-based food behaviour questionnaire, from students in grades 6,7 & 8 from the First Nations communities of Georgina Island, Christian Island, Fort Albany, Attawapiskat, Peawanuck, Moose Factory, Kashechewan and Ouje-Bougoumou (Quebec). HEI-C was assessed as good (81-100), needs improvement (51-80) or poor (0-50). Results: Mean community HEI-C scores ranged from 57.38-70.04, with differences by community (p=0.027) and season (p=0.007); more northerly communities seemed to have lower HEI-C scores and fall seemed to have higher HEI-C scores compared to winter and spring. A non-significant negative correlation between BMI and HEI-C was observed (r=-0.107, NS). As percent energy from ‘other foods’ increased, the HEI-C score tended to decrease. Game consumption appeared to contribute to higher HEI-C scores. Eating outside the home did not seem to affect HEI-C. Conclusions: Poor diet quality in remote on-reserve youth populations is a concern. Lack of consistent access to healthy foods may have a negative impact on diet quality. Programs that help improve the provision of healthy foods, decrease the intake of “other foods” and that emphasize game may help to improve diet quality.